Organizational Cultural Practices and Employee Efficiency among Selected Nigerian Commercial Banks - Olanrewaju, Lawal Ibrahim; Westhuizen, Thea Van Der; Awotunde, Olusegun Matthew (Journal of Economics and Behavioral Studies, 2019)
The study examined the relationship between organizational culture and employee efficiency among commercial banks in Nigeria. Primary data was gathered by means of a self administered questionnaire. to select 223 respondents using simple random sampling technique, and out of which 218 were retrieved. the Statistical Package for the Social Sciences (SPSSS) was adopted to analyze collected data. The findings revealed that organizational processes and structures were significant predictors of employee efficiency. As a result, the staff’s familiarity with the organizational processes and structure, their efficiency levels. Arising from these findings, it is recommended that all bank employees should become familiar with and committed to the corporate culture. Appropriate incentives should be offered to employees. These should not be restricted to monetary rewards, but should include recognition of their performance and present opportunities to achieve individual goals and aspirations. Finally, both managers and employees should receive training to enhance efficiency.